English Spoken in the Channel Islands - Elvensø, Signe (Leviathan: Interdisciplinary Journal in English, 2022)
The Channel Islands spoke Norman French up until the 19th century, when English began to take over as the main language of the inhabitants. Today, their local French dialects are dying out, but several features from Norman French are preserved in their English dialect for a while longer. This article examines some of the ways Channel Island English varies from Standard English, and how the dialect has been affected by Norman French by analysing five different features of the dialect: three of them phonological and two of them morphosyntactic. These features have been elected and analysed based on an interview of two native speakers of respectively Jersey English and Guernsey English, produced by BBC in 2015, as well as on findings of previous studies. Though the study, with only two speakers, is not necessarily representative, it does show that the non-standard dialect is present in the Channel Islands.